“Peruvian Olympic Athletes” Campaign. Audiovisual Narrative in Social Advertising - Karbaum Padilla, Gerardo (2016)
In the last two centuries, human society went through radical changes in the way they communicates. Consequence of constantly technology innovation, adverstising became into a main character inside this invigorated context, where all the audiovisual narratives forms evolve to create messages that reach the target attention. But more than commercial objectives, the social message has been developed in order to change attitudes in the entire population on the ad campaigns. These social messages produce some positive thoughts around important issues in society such us health, ecology, education, human rights, etc. and also generated several communicational strategies that leads to their own way for creating, producing or printing/posting/airing advertising which are important and reknown because of its common interests and strategies for narrative construction.